2012
DOI: 10.2217/fmb.12.129
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensing to Adjust Bacterial Virulence in a Fluctuating Environment

Abstract: JournalFuture microbiology RightsArchived with thanks to Future microbiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 207 publications
0
43
0
Order By: Relevance
“…The effect of temperature is important because temperature is often reported to affect the virulence gene expression (26,37). We observed a significant decrease in DNA stiffening at temperatures greater than 30°C (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The effect of temperature is important because temperature is often reported to affect the virulence gene expression (26,37). We observed a significant decrease in DNA stiffening at temperatures greater than 30°C (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Implications of Ler Responses to Environmental Factors-It has been shown that Ler's anti-silencing activity is regulated by environmental factors such as temperature (26,37). Previous studies did not reveal whether this occurs through regulation of Ler⅐DNA binding or through regulation of H-NS⅐DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…10 Most of the characterized transencoded ncRNAs interact with multiple target mRNAs with the assistence of the RNA chaperone Hfq 11 and act in concert with RNases that cleave the target mRNA and control its halflife. 12,13 Other types of riboregulators are RNA thermometers, 14,15 and riboswitches. 16 These sensory RNA elements are found in the 5 0 -untranslated regions (5 0 -UTRs) or within intergenic regions, and control expression of the downstream gene through structural remodeling of the RNA segment.…”
Section: Molecular Mechanisms Underlying Rna-based Control Of Virulencementioning
confidence: 99%
“…Therefore, the production of virulence-associated traits in all cases has to be coupled with the exposure to a temperature of 378C or higher, and at least in the case of Neisseria meningitidis [32] to 428C, as will be discussed further. Thus, bacterial pathogens respond to temperature changes throughout their life cycles and sense structural changes of protein, RNA, and even DNA [35][36][37][38][39][40].…”
Section: Rna Structures That Sense Temperature Changes In Pathogenicmentioning
confidence: 99%
“…Therefore, the production of virulence-associated traits in all cases has to be coupled with the exposure to a temperature of 378C or higher, and at least in the case of Neisseria meningitidis [32] to 428C, as will be discussed further. Thus, bacterial pathogens respond to temperature changes throughout their life cycles and sense structural changes of protein, RNA, and even DNA [35][36][37][38][39][40].A molecular mechanism that couples protein production with bacterial exposure to body temperature in pathogenic bacteria is the presence of RNA structures that block ribosome binding sites (RBSs) of mRNAs at different levels depending on the environmental temperature [41]. These structures are called RNATs, and here we review how they participate in the regulation of expression of virulencerelated traits in bacteria and establish some of the research challenges in this field (Box 1).…”
mentioning
confidence: 99%